Rodzinne i partnerskie uwarunkowania dobrostanu studentów - Jankowiak, Barbara (Studia Edukacyjne, 2020)
Subjective well-being constitutes and important area for positive psychology research. Building own feeling of happiness and satisfaction strongly depends on relations with other people. The aim of this thesis in the analysis of the relations between well-being and family relations or partnership relations of students. The results obtained showed that the retrospective positive evaluation of a relation between parents in the childhood period and own relations with the father were connected to the higher indicators of personal well-being. What has been obtained is also statistically important relation between secure attachment style and higher personal well-being as well as between the styles: evasion and anxiety-ambivalent and lower personal well-being. The prediction analysis proved that both non-secure styles decrease the well-being indicators, however, it did not prove that the secure style is the condition of well-being. With regards to intimate relations, the obtained results point that the form itself of the relations which is formed does not relate to the feeling of happinessbut its quality definitely does. The obtained data also show that the people being in the relationships are more satisfied with life that singles.